2020
DOI: 10.1002/adma.201907499
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stretchable Polymer Composite with Strain‐Enhanced Electromagnetic Interference Shielding Effectiveness

Abstract: Polymer composites with electrically conductive fillers have been developed as mechanically flexible, easily processable electromagnetic interference (EMI) shielding materials. Although there are a few elastomeric composites with nanostructured silvers and carbon nanotubes showing moderate stretchability, their EMI shielding effectiveness (SE) deteriorates consistently with stretching. Here, a highly stretchable polymer composite embedded with a three‐dimensional (3D) liquid‐metal (LM) network exhibiting subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
197
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(199 citation statements)
references
References 46 publications
2
197
0
Order By: Relevance
“…LM has been infused into the pores of existing elastomer foams [17] to create a conductive rather than a dielectric composite. [18] Here, the LM is dispersed in the foam walls and the pores of the foam remain filled with air; we call this porous structure 'liquid metal elastomer foam' (LMEF). The LMEF is extremely soft, has good compressibility, and the ε r changes significantly in response to strain.…”
Section: Introductionmentioning
confidence: 99%
“…LM has been infused into the pores of existing elastomer foams [17] to create a conductive rather than a dielectric composite. [18] Here, the LM is dispersed in the foam walls and the pores of the foam remain filled with air; we call this porous structure 'liquid metal elastomer foam' (LMEF). The LMEF is extremely soft, has good compressibility, and the ε r changes significantly in response to strain.…”
Section: Introductionmentioning
confidence: 99%
“…However, the composites consisting of liquid metal micro/nano particles may demonstrate the stretch-enhanced conductivity [ 54 ]. For example, Wang et al reported that the electrical conductivity of the 3D LM composite increases monotonically with applied tensile strain, from 5.3 × 10 5 S/m under the stretch-free condition to 1.1 × 10 6 S/m at 400% strain ( Figure 3 d) [ 55 ]. Similarly, a liquid metal-filled magnetorheological elastomer shows the minimum conductivity in the relaxed state and increases drastically under any deformation ( Figure 3 e) [ 56 ].…”
Section: Propertiesmentioning
confidence: 99%
“…Copyright (2013) WILEY-VCH. ( d ) Electrical conductivity as a function of the strain of the composites [ 55 ]. Copyright (2020) WILEY-VCH.…”
Section: Figurementioning
confidence: 99%
“…Thus, hardware dielectric materials with low- D k and low- D f characteristics are in demand for the 5G combination construction. Another important developing trend for research and development of 5G telecommunication is the combination with advanced display techniques, such as wearable display, health monitoring display, and so on [ 8 ]. Thus, among the new materials developed for 5G applications, advanced fabrics or fibrous membranes with low- D k and low- D f features have occupied important positions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%